TMDs APPROACH BY STUDENTS AND YOUNG DOCTORS - Alina Mihaela Apostu; Arina-Alice; Magda Antohe; Petronela Bodnar; Larisa Țarevici; Violina Budu; Vlad Ștefan Proca; Oana Țănculescu (Romanian Society of Oral Rehabilitation, 2023)
TMJ disc displacement, which is a relatively frequent pathology, proves to be frustrating experience not only for patients, but also for dentists, who often lack sufficient expertise in this area. Consequently, they tend to refer patients to maxillofacial surgeons. Furthermore, there are instances where dentists are completely unaware of this pathology. Therefore, the aim of this study is to assess the level of knowledge among freshly graduated dental students regarding temporomandibular disorders (TMDs). To achieve this, a questionnaire consisting of multiple-choice questions was administrated to dental students who graduated from the Faculty of Dental Medicine at "Grigore T. Popa" University of Medicine and Pharmacy Iasi within the last two years. The responses yielded unexpected results, both positive and negative, leading to various conclusions. It became evident that general dentists possess limited knowledge about temporomandibular disorders. To address this issue, universities should prioritize incorporating comprehensive TMD pathology education, not only during programs addressed to prosthodontic specialists.